Flywheel training: body composition and neuromuscular performance in older women: a pilot study - Yánez, Cristian Andres; Pascagaza, Yenny; Sanclemente, Yeimer; Ochoa, Nestor (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Flywheel training enhances neuromuscular capacity in older adults, improving force production and muscle size while reducing the negative impacts of limb disuse and ageing (sarcopenia and dynapenia) and minimizing the likelihood of injuries or falls. The study evaluated the effects of squat training using flywheel equipment on body composition and neuromuscular performance in older women.Methods. The sample consisted of 14 participants randomly allocated to either a flywheel resistance exercise training group [FWRET; experimental group (EXP), n = 7] who underwent eight weeks of training (one day per week) or a control group (CON; n = 7). Before and after the intervention, countermovement jumps were assessed, and the average power and mean propulsive velocity (MPV) of flywheel training were registered.Results. Within-group analyses demonstrated a significantly better performance in jump variables for the EXP throughout squat training. Between-group analyses showed no improvements in the EXP compared with the CON, and there were no significant differences between groups for body composition. Mean power and MPV increased after FWRET, which were associated with the jump variables.Conclusions. Squat training using flywheel equipment could effectively improve neuromuscular performance and increase explosive strength capacity in older adults.
Keywords: isoinertial exercise; older adults; strength training; resistance; eccentric